Biofertilizers as Strategies to Improve Photosynthetic Apparatus, Growth, and Drought Stress Tolerance in the Date Palm - Anli, Mohamed; Baslam, Marouane; Tahiri, Abdelilah; Raklami, Anas; Symanczik, Sarah; Boutasknit, Abderrahim; Ait-El-Mokhtar, Mohamed; Ben-Laouane, Raja; Toubali, Salma; Ait Rahou, Youssef; Ait Chitt, Mustapha; Oufdou, Khalid; et al. (Frontiers in Plant Science, 2020)
Rainfall regimes are expected to shift on a regional scale as the water cycle intensifies in a warmer climate, resulting in greater extremes in dry versus wet conditions. Such changes are having a strong impact on the agro-physiological functioning of plants that scale up to influence interactions between plants and microorganisms and hence ecosystems. In (semi)-arid ecosystems, the date palm (Phoenix dactylifera L.) -an irreplaceable tree- plays important socio-economic roles. In the current study, we implemeted an adapted management program to improve date palm development and its tolerance to water deficit by using single or multiple combinations of exotic and native arbuscular mycorrhizal fungi (AMF1 and AMF2 respectively), and/or selected consortia of plant growth-promoting rhizobacteria (PGPR: B1 and B2), and/or composts from grasses and green waste (C1 and C2, respectively). We analyzed the potential for physiological functioning (photosynthesis, water status, osmolytes, mineral nutrition) to evolve in response to drought since this will be a key indicator of plant resilience in future environments. As result, under water deficit, the selected biofertilizers enhanced plant growth, leaf water content, and electrical conductivity parameters. Further, the dual-inoculation of AMF/PGPR amended with composts alone or in combination boosted the biomass under water deficit conditions to a greater extent than in non-inoculated and/or non-amended plants. Both single and dual biofertilizers improved physiological parameters by elevating stomatal conductance, photosynthetic pigments (chlorophyll and carotenoids content), and photosynthetic efficiency. The dual inoculation and compost significantly enhanced, especially under drought stress, the concentrations of sugar and protein content, and antioxidant enzymes (polyphenoloxidase and peroxidase) activities as a defense strategy as compared with controls. Under water stress, we demonstrated that phosphorus was improved in the inoculated and amended plants alone or in combination in leaves (AMF2: 807%, AMF1+B2: 657%, AMF2+C1+B2: 500%, AMF2+C2: 478%, AMF1: 423%) and soil (AMF2: 397%, AMF1+B2: 322%, AMF2+C1+B2: 303%, AMF1: 190%, C1: 188%) in comparison with controls under severe water stress conditions. We summarize the extent to which the dual and multiple combinations of microorganisms can overcome challenges related to drought by enhancing plant physiological responses.